Construção de vídeo educativo para promoção da saúde visual de escolares - Rodrigues Junior, Janio Cavalcanti (2014)
Educational video can become a valuable resource in identifying visual impairment in students. The objective was to make an educational video for early detection of visual impairment in school children. Study is a technolog y development type that three stageswerefollowed: pre-production (preparing the v ideo script and content validation of the video script); production (video recording); and po st-production (video editing). Script preparation was through integrative review conducte d in March and April of 2014. Its first version was submitted to validation of nine content experts (health professionals) and five technical experts (area of communication / cinema) from June to October 2014. The study was approved by the Ethics Committee of the Univers idade Federal do Ceará under the Opinion nº 666,360. About the overall evaluation of the video, the script was considered valid by all the experts. It can be seen that four (44.4% ) of experts have approved the content of the video script and five (55.5%) have approved with mo difications. As for technical experts, three (60%) have considered it approved with modifi cations, while two (40%) judged it as approved. Among the suggested changes, there was a decrease in the number of scenes that was incompatible with the proposed time; replacemen t of technical terms for colloquial language and recreational settings; expansion of be haviors which reflect difficulty in seeing; decrease in the number of behaviors performed by a single character; insertion scene which shows improvement of the child after the optical co rrection. The recordings were made in a public school in Fortaleza and in the LabCom_Saúde in October, 2014. During the post- production, changes were suggested to the extent, a udio and aesthetic factors, including: increased supply of characters; Replacement of phot os by images compatible with the regional reality and video clippings; overlapping o f concomitant keywords with the appearance of the images in voice off ; and audio homogenization of the characters on sta ge and off . All suggestions were accepted on the issue, which was completed with 16 minutes and 14 seconds, including credits, appropriate time to educational videos. It is believed that this educational technology incorporated into inter ventions and health professional guidelines enabled have contributed to the target public's und erstanding about visual health, with the implication of early diagnosis of visual impairment to resolve the problems.